Using ICT and distance education to increase access, equity and quality of rural teachers’ professional development - Bernadette Robinson (International Review of Research in Open and Distributed Learning, 2008)
The goal of ‘teacher quality for all’ is proving difficult to achieve in many countries, especially in rural areas, yet teacher quality is a key determinant of students’ participation rates and achievement levels. It also affects the attainment of social justice in terms of equity in educational quality for students. One contributor to teacher quality is professional development though limits on its availability and quality create inequity for many teachers. This paper describes how distance education and ICT improved access, equity, and quality in professional development for rural teachers in one province in western China, viewed through the lens of a ‘rights-based’ framework.